Integrating Behavioural and Branding Perspectives to Maximize Green Brand Equity: A Holistic Approach. (30th September 2016) - Butt, Muhammad Mohsin; Mushtaq, Saadia; Afzal, Alia; Khong, Kok Wei; Ong, Fon Sim; Ng, Pui Fong
Abstract: The aim of this study is to expand the existing understanding of green consumers' behaviour by proposing and testing an integrated conceptual model that explores the influence of consumers' personal concerns for the environment and general attitudes towards green products on brand‐related knowledge structures (image and associations) and relationship preferences (trust and brand equity) for green brands. A questionnaire‐based survey method was used to collect data using convenience sampling. One hundred and ninety‐nine usable responses were obtained. A structural equation modelling procedure was used to test the proposed hypotheses. The results confirmed that a positive relationship exists between consumer concern for environmental values and general attitudes towards green products. Both these constructs influence consumers' knowledge structure of a green brand (image and associations). Furthermore, a strong relationship exists between consumers' knowledge structure (image and associations) and their relational preference (trust and brand equity) with green brands. These findings are important for business strategy formulation by providing empirical support for the idea that a firm should invest its resources not only to project its environmentally friendly brands but also to build consumers' concern for environmental values and their attitude towards green products. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment